Rapid increase in immunoreactivity to GFAP in astrocytes in vitro induced by acidic pH is mediated by calcium influx and calpain I - Lee, YB; Du, S; Rhim, H; Lee, EB; Markelonis, GJ; Oh, TH (ELSEVIER SCIENCE BV, 2000)
In higher vertebrates, reactive gliosis resulting from injury to the central nervous system (CNS) is characterized by a rapid increase in immunoreactivity (IR) to glial fibrillary acidic protein (GFAP). Little is known about the extracellular signals that initiate the increase in GFAP-IR following CNS injury. We demonstrated recently [T.H. Oh, G.J. Markelonis, J.R. Von Visger, B. Balk, M.T. Shipley, Acidic pH rapidly increases immunoreactivity of glial fibrillary acidic protein in cultured astrocytes, Glia 13 (1995) 319-322] that a rapid increase in GFAP-IR can be evoked in mature astrocyte cultures by exposing the cells to an acidic medium. We investigated the intracellular pathway(s) involved in initiating increased GFAP-IR, a hallmark of reactive astrocytes. The increase in GFAP-IR produced by exposure to acidic medium was blocked by pretreatment with nickel ions, by such blockers of L-type calcium channels as nifedipine, verapamil and diltiazem, by calpain inhibitor I, or by the intracellular calcium chelator, BAPTA-AM. At physiological pH, treatment with the calcium ionophore, A23187, resulted in increased GFAP-LR which could be blocked by pretreatment with calpain inhibitor I. Astrocytes exposed to low pH exhibited a marked increase in a GFAP fragment with a molecular weight of 48 kDa. In astrocytes exposed to acidic medium, cr-fodrin, a selective endogenous substrate of calpain, was also found to be hydrolyzed producing fragments with molecular weights of 120-158 kDa. As anticipated, pretreatment with calpain inhibitor I prevented the proteolytic degradation of both GFAP and oc-fodrin in these samples. These results suggest that the initial increase in GFAP-IR after CNS injury appears to be linked to Ca++ influx, and is mediated further by a proteolytic process that seemingly involves the activation of the calcium-dependent protease, calpain I. (C) 2000 Elsevier Science BN. All rights reserved.
Keywords: SPINAL-CORD INJURY; EXPERIMENTAL AUTOIMMUNE ENCEPHALOMYELITIS; MESSENGER-RNA; CULTURED ASTROCYTES; NEURONAL-ACTIVITY; INDUCED SEIZURES; ALPHA-FODRIN; CATHEPSIN-B; STAB WOUNDS; RAT-BRAIN